Optical and Spectroscopic Properties of Ho:Lu2O3 Transparent Ceramics Elaborated by Spark Plasma Sintering - Lucas Viers; Simon Guené-Girard; Gilles Dalla-Barba; Véronique Jubéra; Éric Cormier; Rémy Boulesteix; Alexandre Maître (Ceramics, 2024)
In this work, transparent ceramics were manufactured from nanopowders synthesized by aqueous coprecipitation followed by Spark Plasma Sintering (SPS) to ensure rapid and full densification. The photoluminescence of Ho:Lu2O3 transparent ceramics was studied in the Visible and IR domains as a function of Ho3+ dopant level from 0.5 at.% to 10 at.%. A cross-relaxation mechanism was identified and favors the 2 μm emission. All of the obtained results indicate that the optical properties are very similar between Lu2−xHoxO3 transparent ceramics and single crystals. Thus, the SPS technique appears to be a very promising method to manufacture such ceramics, which could be used as amplifier media for high-energy solid-state lasers.